Does Local Financial Development Matter? - Guiso, L.; Sapienza, P.; Zingales, L. (Quarterly Journal of Economics, 2004)
We study the effects of differences in local financial development within an integrated financial market. We construct a new indicator of financial development by estimating a regional effect on the probability that, ceteris paribus, a household is shut off from the credit market. By using this indicator, we find that financial development enhances the probability an individual starts his own business, favors entry of new firms, increases competition, and promotes growth. As predicted by theory, these effects are weaker for larger firms, which can more easily raise funds outside of the local area. These effects are present even when we instrument our indicator with the structure of the local banking markets in 1936, which, because of regulatory reasons, affected the supply of credit in the following 50 years. Overall, the results suggest local financial development is an important determinant of the economic success of an area even in an environment where there are no frictions to capital movements.